Faktor-Faktor yang Mempengaruhi Keputusan Nasabah Bertransaksi di Bank Syariah (Studi Kasus di Bank Syariah Mandiri Cabang Boyolali) - Ma'arif, Saiful, Dra. Rina Trisnawati Ak., M.Si Ph.D (2016)
This research aimed to know the influence factor customer decision transaction at Bank Syariah Mandiri.the research population is all costumer Bank Syariah Mandiri boyolali branch office, with sample research as much as 100 respondents. Dataanalisis technique used is multiple linier regression analisys. The results showed that. 1) The revenue share does not significantly influence for customer's decision transaction 2) The location significantly influence the customer's decision transaction. 3) Confidence / religion significantly influence the customer's decision transaction. 4) The service does not significantly influence the customer's decision transaction.